Scots tee up for semiconductor drive. - Goldstein, H. (IEEE spectrum)
Sheep, shipbuilding, and steel were at the core of Scotland's economy for most of the 20th Century. But in the early 1990s, when the shipyards and steelworks fell silent, the Scots looked to Silicon Valley for a model of how to pair venture capital with entrepreneurs. Their hope was that technical ideas coming out of the country's prestigious universities could be brought to market. Initially that strategy met with some success, but some ventures are now beginning to fall by the wayside.